Integrated circuit manufacturability : (IEEE Press, 1999)
"Integrated circuit manufacturability" provides comprehensive coverage of the process and design variables that determine the ease and feasibility of fabrication (or manufacturability) of contemporary VLSI systems and circuits. This book progresses from semiconductor processing to electrical design to system architecture. The material provides a theoretical background as well as case studies, examining the entire design for the manufacturing path from circuit to silicon. Each chapter includes tutorial and practical applications coverage.